Treatment of Second and Third Degree of Hemorrhoid by Laser Procedure - مرتضى, أيمن (Latakia University Journal -Medical Sciences Series, 2020)
Hemorrhoids are a common anorectal condition with a major medical and socioeconomic impact. Owing to the high incidence of hemorrhoids in the adult population together with the risk of complications of traditional treatment. The aim of our study was to present our experience with laser procedure to treat 2- and 3-degree hemorrhoids with absent or minimal mucosal prolapse. Our study included 150 patients with 2 and 3 degree of symptomatic hemorrhoids who underwent to a medical center in Latakia city in 2017-2019. Data were collected on clinical and outcome. some of this result were compared with global studies. Our study included 100 male and 50 female patients of mean age 40 years. Hundred and ten patients had bleeding and 40 patients had hemorrhoidal syndrome. Mean operative time was 25± 5 minutes. Patients were discharged home within a mean 240 ± 60 minutes and allowed to resume normal activities on the first day post operation. Intraoperative bleeding occurred in 20 patients (13,3%). 1-2-day post operation, bleeding occurred in 3 patients. Hemorrhoidal thrombosis formed in in 10 patients 6,66%. At the six months follow – up, no complications were reported, and there was significant improvement in symptoms. No pain reported on week post operation in 73,3% of patients. Patients with 2- and 3-degree hemorrhoids with or absent minimal mucosal prolapse, treated by laser procedure had an excellent outcome in term of resolution of symptoms and postoperative pain. Minor complications occurred intraoperation. No negative results or recurrence had been noted after six months post operation and this is important when compared to traditional surgery.